Hydatidosis cases in one of Mar del Plata City hospitals, Buenos Aires, Argentina - Dopchiz,Marcela Cecilia (2007)
Hydatidosis is a zoonosis of worldwide distribution produced mainly by the metacestode Echinococcus granulosus. In Argentina, its distribution reaches endemic levels. The aims of this investigation were to contribute to the knowledge of hydatidosis in the southeast of Buenos Aires province, study its evolution at the Interzonal General Hospital for Acute Diseases between 1992 and 2002 and discuss its importance. Clinical records of operated and/or diagnosed patients were reviewed with regard to this disease. One hundred and twenty cases were analyzed. Among the patients, 56.7% were women. The average age was 42.2+16.8 years. 68.3% lived in urban areas. In 75% of the cases, ultrasonography was used. Hepatic location was most frequently seen. 89.2% received surgical treatment. Albendazole was used for 19 patients. The mean length of hospital stay was 16 days. We conclude that this zoonosis is a disease that generates high costs in medical care and for this reason more epidemiological studies should be carried out and public health authorities should implement control and prevention strategies in the region.